Donepezil for the Treatment of Language Deficits in Adults With Down Syndrome: A Preliminary 24-Week Open Trial - Heller, James H. (2003)
At present, there is no proven pharmacologic treatment for cognitive or language impairments in Down syndrome (DS). Cholinergic deficits have been documented in DS and linked to cognitive deficits. This study is a 24-week open-label clinical trial of donepezil hydrochloride for the treatment of language deficits in adults with DS. To our knowledge, this is the first prospective study to evaluate systematically the effects of donepezil, a cholinesterase inhibitor, on specific language domains in DS. The main finding that emerged was an improvement in expressive language performance following donepezil therapy. Despite the multiple methodological limitations, the results raise important questions regarding the role of the cholinergic system in language function and the specific effect of cholinergic therapy in the treatment of language impairment in DS. The results support the need for large-scale controlled studies of the effects of donepezil treatment on language and on other cognitive domains in DS.